Determination of chlorhexidine in pharmaceutical topical solutions using fourier-transform infrared spectroscopy-attenuated total reflectance. - Villorente, Zenith (Miag-ao, Iloilo University of the Philippines Visayas, 2018)
Chlorhexidine is a chemical agent with broad-spectrum antimicrobial activity against a wide range of microorganisms commonly infecting the skin. Compendial testing for chlorhexidine, as a requirement for most regulatory submissions around the world, is detailed in the United States Pharmacopeia (USP) as well as in any other available pharmacopeias. The compendium uses the high-performance liquid chromatography (HPLC) method for the quantification assay. This method involves sample preparations, usage of expensive HPLC-grade reagents, and analysis time of approximately 30 minutes per sample. In a manufacturing set-up, a faster, reliable qualitative and quantitative analytical method for the analysis of work-in-progress (WIP) materials is one of the basic needs of the quality control section to cope with the output-based production section. This study aims to develop and validate a method that utilizes FTIR-ATR for the determination of chlorhexidine in topical pharmaceutical solutions. Univariate and multivariate calibration models were employed to validate the propose method. Results showed that multivariate calibration model using Partial Least Squares Regression technique gave a good prediction model (RMSEP = 0.1456, R2 = 0.9564) after Savitsky-Golay signal preprocessing technique has been employed. Using Students t-test, it was concluded that the concentration of chlorhexidine obtained using the proposed method has no significant difference with that obtained from the compendial method. Though results can be considered as preliminary due to the small data set obtained, it can still be concluded that determination of chlorhexidine in pharmaceutical topical solutions using FTIR-ATR is a fast, non-destructive and inexpensive alternative method. It is recommended that additional concentration range should be analyzed using the proposed method to obtain a bigger data set and get a more conclusive result.
Special Problem (Master of Chemistry) -- University of the Philippines Visayas, 2018.
Keywords: Pharmaceutical topical solutions